The Speech Therapy of Cleft Palate Patients as an Oral Rehabilitation - Y. Ogata (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of speech therapy: The patients can get the normal speech until going into the elementary school. This purpose will success through several steps.